Laparoscopic Pancreas-Sparing Subtotal Duodenectomy - Poves, Ignasi; Burdio, Fernando; Alonso, Sandra; Seoane, Agustín; Grande, Luís (JOP. Journal of the Pancreas, 2011)
Context Primary adenocarcinoma of the duodenum is a rare digestive malignancy which is commonly treated by radical surgical resection, pancreaticoduodenectomy being the technique of choice. Complete tumor resection obtaining free margins should be the standard of treatment for primary adenocarcinoma of the duodenum. Segmental duodenal resection is an appropriate operation for selected cases of primary adenocarcinoma of the duodenum of the 3rd and 4th portions of the duodenum. Case report We present the case of a 67-year-old woman suffering from an infra-ampullary large villous polypoid mass affecting the 3rd portion of the duodenum. Multiple endoscopic biopsies did not disclose any malignancy, and abdominal CT and endoscopic ultrasound found no extraduodenal involvement. A 3rd and 4th portion pancreas-sparing duodenectomy was carried out using a totally laparoscopic approach. Intra-operatory duodenoscopy was done to safeguard the papilla of Vater. Recovery was uneventful and the patient was discharged on the 7th postoperative day. The final diagnosis was primary adenocarcinoma of the duodenum (free resection margins). After forty-five months of follow-up, the patient is free of disease. Conclusions We recommend this procedure for treatment of an infra-ampullary benign and pre-malignant duodenal pathology; it can also be a treatment option and an alternative to a pancreaticoduodenectomy in very selected cases of tumors confined to the duodenum. Expertise in both pancreatic surgery and laparoscopic techniques is required. Image: Sectioning of the duodenum infrapapillary under endoscopic control view.